Associated factors of myopia in a Portuguese sample of adolescents: Parental history and school-related lifestyle - Amélia Fernandes Nunes; Mariana Cunha; Dário Ferreira; Miguel Castelo-Branco Sousa; Cristina Albuquerque Godinho (PLoS ONE, 2026)
Purpose This study aimed to investigate the interaction between parental myopia and school-related lifestyle patterns, and myopia in a sample of Portuguese adolescents. Based on previously reported data, we examined whether environmental and behavioural correlates traditionally associated with myopia, such as outdoor time, physical activity practice, screen time, and academic load, maintain their significance in a non-metropolitan European context. Methods This analysis involved a sample of 874 adolescents (10−18 years). Myopia was measured using non-cycloplegic open-field autorefraction and defined as a spherical equivalent ≤ −0.50D in the worse eye. Potential factors correlated with myopia were collected through supervised questionnaires completed by students and parents. Data were analysed using univariate and multivariable logistic regression to identify independent associations adjusting for demographic and behavioural covariates. Results The prevalence rate of myopia was 22.5%. The multivariable model identified family history of myopia as the strongest association (OR up to 3.75; CI:2.03–6.95; p < 0.001). Attending a higher school level (OR=2.20; CI:1.07–4.52; p = 0.032) and schools in urban locations (OR=1.59; CI:1.00–2.50; p = 0.048) showed a significant association. Regarding lifestyle, regular physical activity (≥ 2 times per week) was associated with odds of myopia (OR=0.47; CI:0.29–0.77; p = 0.003) even after adjustment for parental history of myopia. Although included in the fully adjusted model, factors such as smartphone use and breastfeeding did not reach statistical significance (p > 0.05). Conclusions Despite the low population-density environment in this region, myopia prevalence was comparable to that reported in other European studies. The identified associations suggest that both parental history and school-related lifestyle factors should be considered when interpreting myopia patterns in adolescence. These findings may help inform school-based strategies aimed at promoting healthier visual and behavioural habits.